Find A so that


5log(base5)16807 − 3log(base5)7 = log (base5)A

I don't even know how to start this one...should I remove the 5 and 3 in front of the logs?

3 answers

log5 16807^5 - log57^3 = log5A
log5 (16807^5/7^3) = log5A

A = 16807^5 / 7^3
= 49(16807)^4
= appr 3.91 x 10^18
oh right you just have to factor out the logbase5...thank you
You are NOT factoring it out
You are saying that if
log x = log y
then x = y
Similar Questions
  1. Hi, same ques. again1/3log(base5) 3x + log(base5) 4=3 If the starting is this: log(base5)3x^1/3+log(base5)4=3 What would be the
    1. answers icon 2 answers
  2. Need help with these:Write the expression as a logarithm of a single quality. a) 3log[base5](a) + 4log[base5](b) -
    1. answers icon 2 answers
  3. Expand the logarithmic expression.log57a5 (1 point) Responses log57 • 5log5a log 5 7 • 5log 5 a log57 + 5log5a log 5 7 +
    1. answers icon 1 answer
  4. 8. Which of the following expressions is equivalent to (-7)^5-7 * -7 * -7 * -7 * -7 -7 * 5 (-7) * 7 * (-7) * 7 * -7 5 * 5 * 5 *
    1. answers icon 8 answers
more similar questions